Prevalence and association of atherosclerosis at three different arterial sites in patients with type III hyperlipoproteinemia - Dobmeyer, Jürgen; Lohrmann, Jens Dieter Wolfgang; Feussner, Giso (Atherosclerosis, 1996)
We have examined the prevalence of clinically significant atherosclerosis in 78 patients with type III hyperlipoproteinemia (HLP) and homozygosity for apolipoprotein (apo) E2. Forty-six of these individuals (59%) had no atherosclerosis, 32 patients (41%) had atherosclerosis, i.e., atherosclerosis of the extracranial carotid arteries (CAA), coronary arteries (CAD) or/and peripheral arteries of the legs (PVD), either singly or in combination. No association could be shown with respect to the co-prevalence of atherosclerotic lesions at these different arterial sites, except for the high predictive value (pv = 0.88, P = 0.006) of CAA for the presence of PVD. Hence, documentation of atherosclerosis under clinical aspects at one of these exposed arterial territories does not allow a reliable prediction of generalised atherosclerosis or local atherosclerosis at other sites of the arterial tree in individuals with this familial lipoprotein disorder. Therefore, assessment of the extent of clinically significant atherosclerosis in type III HLP patients should include careful and thorough examination of the extracranial carotid arteries, the coronary arteries, and the peripheral arteries of the legs.